Reflections on methodology sociology, ethnography and applied research - Travers, Max 1961- (Routledge, 2025)
Reflections on Sociology provides an engaging retrospective on the career of Max Travers, exploring key ethnographic projects and fundamental methodological debates in social science
Keywords: Crime & criminology; Forschungsmethoden, allgemein; PSYCHOLOGY / Social Psychology; REFERENCE / Research; Research methods: general; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Sociology / General; Social & cultural anthropology, ethnography; Social, group or collective psychology; Sociology: customs & traditions; Sozial- und Kulturanthropologie, Ethnographie; Sozialpsychologie; Soziologie; Verbrechen und Kriminologie (Kriminalistik)